Development of an Agricultural Legal Entity and Reorganization of Regional Agriculture in the Tonami Plain - OTAKE, Nobuo (Chirigaku hyōron, 2008)
This study investigated the process of reorganization mainly done by an agricultural legal entity in a paddy field rice-growing area. To make the present Japanese paddy field rice-growing under postproductivism sustainable, it is necessary to reorganize areas with new systematization of production. This research clarified the management conditions of S-nousan enterprise with large-scale paddy field rice-growing operations and the method of accumulating farmland in the Tonami plain, where the wage rate of part-time farmers and the cost of managing a small-scale farmhouse are high. The problems of Japanese paddy field rice-growing under postproductivism are reducing the amount of abandoned cultivated land, finding workers for regional farming, and making agricultural multifunctionality work well. Influenced by the decreased price of rice and the expansion of the production adjustment rate, modern Japanese paddy field rice operations face such difficulties as the decrease in number of farmers and the outdated management of farms. S-nousan enterprise tried to produce original rice to meet consumer demand, reduce machinery costs, and expand management scale, playing an important part in regional agriculture. As the example of this enterprise shows, making Japanese paddy field rice-growing areas sustainable with the severe shortage of successors requires systematizing agricultural management in the entire area and reorganizing regional agriculture into a single unit under that system. In addition, it is important for the entity promoting regional agriculture to have clear management strategies appropriate for the actual circumstances and systematize production while maintaining a cooperative system in the area.